Optimizing the Potential of Local MSMEs to Improve the Economy of Rancakole Village Through the MSME Festival - Malik, Miftahul; Laragianti, Rita; Fauziah, Azmy Restu; Sabrina, Janua; Nurajijah, Ai; Pertiwi, Dewi Sri; Fitriyani, Bilqis Salbiyyah; Pratama, Raihan Wahyu; Kahfi, Rifki Solehudin; Ma'ripah, Leli Laelatul; Eulisnawati, Eulisnawati (CV. Rayyan Dwi Bharata, 2025)
Real Work Lecture (KKN) activities are an important part of higher education in Indonesia which integrates academic theory with direct practice in society. In its implementation in Rancakole Village, Arjasari District, Bandung Regency, UNINUS KKN group 36 students focused on developing the local economy through the MSME Festival. This festival was held as a response to the economic problems experienced by housewives in RW 20, who have the skills to process agricultural produce into food products but experience difficulties in marketing and capital. The approach applied in this activity includes participatory-based community empowerment and local potential. The results of this activity show an improvement in the community’s economy, increased creativity in product development, and the opening of wider market access. However, challenges such as limited capital and knowledge of digital technology are still obstacles that need to be overcome through long-term solutions, such as the formation of cooperatives and further training.